Social-emotional learning competencies by Anne Frank - Uşakli, Hakan (Educational Challenges, 2025)
Purpose. The aim of this study is to introduce social-emotional learning competencies by analyzing Anne Frank’s diaries. Social-emotional learning (SEL) is based on emotional literacy. Anne Frank, who was murdered in the Holocaust, wrote a total of 189 diaries between June 12, 1942, and August 1, 1944. In her diaries, written with maturity unexpected for her age, Frank effectively analyzed and expressed her own feelings, behaviors, the feelings and behaviors of the people around her, and the events that took place during World War II. In this qualitative study based on document analysis, Anne Frank’s diaries were meticulously analyzed by nine experts and evaluated according to social emotional learning skills. Social-emotional learning, is based primarily on emotional literacy. Methodology. This study was analyzed with the document analysis technique, one of the qualitative research methods. Results. The analysis shows that Anne Frank’s diaries reflect one or more of the following SEL skills: self-awareness, self-management, social awareness, relationship skills and responsible decision-making. Conclusions. Anne Frank’s diaries represent strong emotional literacy skills. Each diary was evaluated in the skill category in which it was most frequently included. There is a need for further studies to examine the Anne Frank Diary of a Young Girl in terms of other psycho-educational studies such as assertiveness, self-esteem and feminist skills.